STRENGTHENING THE STABILITY OF LOCAL BUDGET REVENUES AND ENSURING THEIR EFFICIENT MANAGEMENT - Yuldashev Javohirbek Ikromjon ogli, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
One of the most important directions of the large-scale economic and financial reforms being carried out in our country is the expansion of the revenue base of local budgets, ensuring their stability, and managing them effectively. Local budgets constitute the main part of the state budget, and through them social protection of the population, financing of regional infrastructure facilities, and development programs are implemented. Therefore, the increase in the revenues of local budgets directly affects not only the country’s socio-economic development as a whole but also the sustainable development of the regions.